2009
DOI: 10.1016/j.ijpara.2009.02.020
|View full text |Cite
|
Sign up to set email alerts
|

The protozoan parasite Theileria annulata alters the differentiation state of the infected macrophage and suppresses musculoaponeurotic fibrosarcoma oncogene (MAF) transcription factors

Abstract: The tick-borne protozoan parasite Theileria annulata causes a debilitating disease of cattle called Tropical Theileriosis. The parasite predominantly invades bovine macrophages (mϕ) and induces host cell transformation by a mechanism that has not been fully elucidated. Infection is associated with loss of characteristic mϕ functions and phenotypic markers, indicative of host cell de-differentiation. We have investigated the effect of T. annulata infection on the expression of the mϕ differentiation marker c-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
3
13
0
Order By: Relevance
“…A similar profile has been described in other studies and was associated with repression of high level expression of genes induced by cellular activation, macrophage differentiation or the inflammatory response, that may be detrimental to the parasite infected cell [15], [17]. Taken together, the data indicated that only approximately 6% of differentially expressed genes in TBL20 cells show a sustained trend associated with reversion to the BL20 phenotype although >30% show evidence of immediate susceptibility to parasite death.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…A similar profile has been described in other studies and was associated with repression of high level expression of genes induced by cellular activation, macrophage differentiation or the inflammatory response, that may be detrimental to the parasite infected cell [15], [17]. Taken together, the data indicated that only approximately 6% of differentially expressed genes in TBL20 cells show a sustained trend associated with reversion to the BL20 phenotype although >30% show evidence of immediate susceptibility to parasite death.…”
Section: Resultssupporting
confidence: 85%
“…These results imply that parasite infection may target regulators of the host cell gene expression network as a primary mechanism to alter host cell phenotype. Altered expression of factors (HOX, LMO2, RUNX and SMAD) and networks (MYB) involved in regulation of haematopoetic cell fate decisions [75] is clearly evident, supporting previous work indicating that parasite-mediated transformation is associated with a de-differentiated myeloid type cell [17]. It is accepted that transcription factors and modulation of chromatin status operate to produce stable changes to cellular phenotype [54], [75].…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…31,No. 7 molecules, including nitric oxide and TNF-a [69]. They also upregulate several cytokines that are known to play a crucial role in immune responses against parasites [70,71].…”
Section: Immune Evasion and Inflammation In Theileria-infected Cellsmentioning
confidence: 99%